Structural Strength Analysis of Floor Pan Battery Electric Vehicle Class Medium MPV Using Finite Element Method - Muhammad Hafiz Izzuddin; Widya Aryadi; Haris Nubli (Universitas Negeri Semarang, 2026)
This study aims to analyze the strength of the floor pan structure on the Battery Electric Vehicle medium MPV class using the finite element method. Simulations were carried out with Ansys 2020 software through static loading that was adjusted to the actual conditions of the vehicle. Floor pan design variations were studied based on the type of material, namely JIS G3101 SS400 (M1) and ASTM A1011 Grade 45 (M2), as well as material thicknesses of 1.2 mm (T1), 1.4 mm (T2), and 1.6 mm (T3). The simulation results show that increasing the material thickness decreases the von mises stress and displacement values, and increases the safety factor. ASTM A1011 Grade 45 material shows better structural performance than JIS G3101 SS400, with smaller displacement and higher safety factor at the same thickness. However, the increase in thickness also results in an increase in the mass of the floor pan. Based on the analysis, the M2T1 model is the best configuration because it produces a von mises stress of 161.68 MPa, displacement of 6.6796 mm, safety factor of 1.9174, and mass of 138.25 kg. This model meets the safety limit and mass efficiency, so it is recommended to be applied to the BEV medium MPV.